Pertanian dan Irigasi Kolonial di Bone, 1911-1942 - Suardi, Suratman; Amir, Amrullah; Mappangara, Suriadi (Universitas Hamzanwadi, 2023)
In the early decades of the 20th century, the Dutch East Indies government implemented the